2013
DOI: 10.5402/2013/619754
|View full text |Cite
|
Sign up to set email alerts
|

Development of Self-Management Scale for Kidney Transplant Recipients, Including Management of Post-Transplantation Chronic Kidney Disease

Abstract: An evaluation scale is indispensable for the promotion of continuing, effective postkidney transplantation self-management behaviors. We aimed to develop and validate a new self-management scale for kidney transplant recipients to improve their long-term outcomes and prevent the recurrence of CKD complications. Two hundred and thirty-nine Japanese patients who had undergone kidney transplantation were recruited from three hospitals. The scale's validity and reliability were evaluated using exploratory factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A survey-based study showed that the degree of adherence to transplantation regimens is negatively correlated with time since transplantation. 19 Improving patient self-management may increase adherence to transplantation regimens, thus improving long-term transplant outcomes and reducing the occurrence of complications. 20,21 It has been suggested that patient education alone is not sufficient to improve clinical outcomes but should also be combined with behavioral change.…”
Section: Discussionmentioning
confidence: 99%
“…A survey-based study showed that the degree of adherence to transplantation regimens is negatively correlated with time since transplantation. 19 Improving patient self-management may increase adherence to transplantation regimens, thus improving long-term transplant outcomes and reducing the occurrence of complications. 20,21 It has been suggested that patient education alone is not sufficient to improve clinical outcomes but should also be combined with behavioral change.…”
Section: Discussionmentioning
confidence: 99%
“…46 In a study of kidney transplant patients, the degree of adherence to self-management regimens is negatively correlated with time after transplantation. 47 Thus, participation in decision-making or possessing a high level of self-management skills can positively affect kidney transplant longevity.…”
Section: Discussionmentioning
confidence: 99%
“…The self-management scale is the first scale to be applied as a preliminary test in kidney transplant recipients. [ 21 ] Turkish version of the 4-point Likert scale includes 13 items. Scale items are scored as 1”never applied”, 2 “applied slightly”, 3 “applied very often” and 4 “fully applied”.…”
Section: Methodsmentioning
confidence: 99%